Phylogeny and spatiotemporal dynamics of hepatitis E virus infections in wild boar and deer from six areas of Germany during 2013–2017. Issue 5 (9th April 2022) - Schotte, Ulrich; Martin, Annett; Brogden, Sandra; Schilling‐Loeffler, Katja; Schemmerer, Mathias; Anheyer‐Behmenburg, Helena E.; Szabo, Kathrin; Müller‐Graf, Christine; Wenzel, Jürgen J.; Kehrenberg, Corinna; Binder, Alfred; Klein, Günter; et al.
Abstract: The hepatitis E virus (HEV) can cause acute and chronic hepatitis in humans. Infections with the zoonotic HEV genotype 3, which can be transmitted from infected wild boar and deer to humans, are increasingly detected in Europe. To investigate the spatiotemporal HEV infection dynamics in wild animal populations, a study involving 3572 samples of wild boar and three deer species from six different geographic areas in Germany over a 4‐year period was conducted. The HEV‐specific antibody detection rates increased between 2013–2014 and 2016–2017 in wild boar from 9.5% to 22.8%, and decreased in deer from 1.1% to 0.2%. At the same time, HEV‐RNA detection rates increased in wild boar from 2.8% to 13.3% and in deer from 0.7% to 4.2%. Marked differences were recorded between the investigated areas, with constantly high detection rates in one area and new HEV introductions followed by increasing detection rates in others. Molecular typing identified HEV subtypes 3c, 3f, 3i and a putative new subtype related to Italian wild boar strains. In areas, where sufficient numbers of positive samples were available for further analysis, a specific subtype dominated over the whole observation period. Phylogenetic analysis confirmed the close relationship between strains from the same area and identified closely related human strains from Germany. The results suggest that the HEV infection dynamics in wild animals is dependent on the particular geographical area where area‐specific dominant strains circulate over a long period. The virus can spread from wild boar, which represent the main wild animal reservoir, to deer, and generally from wild animals to humans.